2010
DOI: 10.1007/s11033-010-0416-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SNPs within the sheep PROP1 gene and their effects on wool traits

Abstract: Regarding mutations of PROP1 (Prophet of POU1F1) gene significantly associating with combined pituitary hormone deficiency (CPHD) in human patients and animals, PROP1 gene is a novel important candidate gene for detecting genetic variation and growth, reproduction, metabolism traits selection and breeding. The aim of this study was to detect PROP1 gene mutation of the exon 1-3 and its association with wool traits in 345 Chinese Merino sheep. In this study, on the basis of PCR-SSCP and DNA sequencing methods, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In this study, we detected one SNP located in the 20.9 Mb regions on OAR25. Moreover there were one QTLs detected on OAR5 and OAR6, respectively [5] , [48] . However, in this study, there were no significant SNP markers identified on these chromosomes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, we detected one SNP located in the 20.9 Mb regions on OAR25. Moreover there were one QTLs detected on OAR5 and OAR6, respectively [5] , [48] . However, in this study, there were no significant SNP markers identified on these chromosomes.…”
Section: Resultsmentioning
confidence: 97%
“…The limitations of QTL mapping using linkage analysis (LA) and/or linkage disequilibrium (LD), based on panels of low to moderate-density markers, have been well documented [2] , [3] . Only a few major genes, e.g., the KRTAP6 gene (keratin-associated protein 6) [4] , the PROP1 gene (PROP paired-like homeobox 1) [5] and ADRB3 (beta3-adrenergic receptor) [6] , have been associated with wool traits using QTL linkage analyses or candidate gene studies.…”
Section: Introductionmentioning
confidence: 99%
“…35 Polymorphisms in this gene have been associated with production traits in livestock animals, such as cattle, 40 goats 41,42 and sheep. 43 The marker f68558 is probably not the causal locus that is responsible for growth trait variation in C. farreri . Instead, we think it is more likely that f68558 is in tight linkage disequilibrium with the causal mutation that is possibly located in the regulatory region (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There were three mutation sites of P2 site in RXRG that were G, T and A by comparing with the reported ovis aries RXRG sequences, respectively, among which AAgenotype with an A → G mutation in 131bp and BB-genotype with a G → A mutation in 32bp were not cause amino acid changes. However, these mutations were not correlated with protein expression and therefore these mutations had not influenced gene translation [19] . Association analysis between genotype effect and twinning trait in China Merino sheep found that P2 mutation rate was higher, which showed that there were significant differences in the genotype distribution of among singleton and twins groups (P<0.05) and the different genotypes have a greater impact on the phenomenon of sheep twins that suggested that RXRG could affect the twinning trait in China Merino sheep.…”
Section: Discussionmentioning
confidence: 94%